System dynamics model for high‐speed railway operation safety supervision system based on evolutionary game theory. (2nd October 2018) - Li, Kehong; Zhang, Yadong; Guo, Jin; Ge, Xiaocheng; Su, Yuebin
Summary: In view of the entrusted transportation management model of High‐Speed Railways (HSR) in China, some questions have been exposed during its operation (eg, the supervision and inspection power of HSR company is not fully implemented, the poor management of safety investments, and no incentive and restraint mechanism). Through the analysis of the current situation of the HSR safety supervision system, a system dynamics (SD) model that is composed of an HSR company, the State Railway Administration (SRA) and the commissioned Railways Bureau (RB) have been established based on evolutionary game theory. The behavioral characteristics and the steady state of the decision‐making of all parties involved in the system are proved by the combination of evolutionary game theory and a system dynamics simulation. The results show that, under the clear incentive and restraint mechanism assumptions, the safety supervision and inspection rate of the system has been effectively improved and the supervision power of HSR company has been implemented.